A novel architecture of a bidirectional bridgeless interleaved converter for EV battery chargers - Monteiro, Vítor Duarte Fernandes (2015)
This paper presents a novel architecture of a bidirectional bridgeless interleaved converter for battery chargers of electric vehicles (EVs). The proposed converter is composed by two power stages: an ac-dc converter that is used to interface the power grid and the dc-link, and a dc-dc converter that is used to interface the dc-link and the batteries. The ac-dc converter is an interleaved bridgeless bidirectional boost-type converter and the dc-dc converter is a bidirectional buck-boost-type converter. The proposed converter works with sinusoidal grid current and with high power factor for all operating power levels, and in both grid-to-vehicle (G2V) and vehicle-to-grid (V2G) operation modes. In the paper is described in detail the proposed converter for EV battery chargers: the circuit topology, the principle of operation, the power control theory, and the current control strategy. Several simulation results for both G2V and V2G operation modes are presented.